Identifikasi Dan Karakterisasi Asap Cair Hasil Pirtolisis Limbah Potongan Rambut Manusia Asli Papua - Bogar, Rambert Romeo; Anom, I Dewe Ketut; Saiya, Abdon (General Chemistry Journal, 2024)
Human hair clippings are one of the most common types of waste found in various places. One of the abundant sources of waste, especially in barbershops and hair care related industries. The problem with human haircut waste is the lack of processing of human haircut waste so that it can pollute the environment if it is simply thrown away or burned. The aim of this research is to convert human haircut waste into liquid smoke, analyzing the physical and chemical properties of liquid smoke resulting from pyrolysis of human haircut waste from native Papua. The results of observations of pyrolysis of human hair cuttings were carried out by heating to a temperature of around 80oC-280oC. The physical properties of liquid smoke resulting from pyrolysis of native Papuan human hair clippings are: calorific value 8,028 cal/gr, viscosity 21.047 cSt, density 0.9939 g/ml, flash point 34.2oC, smoke point 176.1oC, boiling point 146.7oC, freezing point -14.2oC. KG-SM analysis of liquid smoke resulting from pyrolysis of native Papuan human hair clips produced 30 chemical compound peaks. From these results it can be concluded that pyrolysis of 915 g of human haircut waste resulted in a total yield of 75 g by weight of liquid smoke